Functional Versatility and Molecular Diversity of the Metabolic Map of Escherichia coli - Tsoka, Sophia; Ouzounis, Christos A. (Genome Research, 2001)
We have analyzed the known metabolic enzymes of Escherichia coli in relation to their biochemical reaction properties and their involvement in biochemical pathways. All enzymes involved in small-molecule metabolism and their corresponding protein sequences have been extracted from the EcoCyc database. These 548 metabolic enzymes are clustered into 405 protein families according to sequence similarity. In this study, we examine the functional versatility within enzyme families in terms of their reaction capabilities and pathway participation. In addition, we examine the molecular diversity of reactions and pathways according to their presence across enzyme families. These complex, many-to-many relationships between protein sequence and biochemical function reveal a significant degree of correlation between enzyme families and reactions. Pathways, however, appear to require more than one enzyme type to perform their complex biochemical transformations. Finally, the distribution of enzyme family members across different pathways provides support for the “recruitment” hypothesis of biochemical pathway evolution.
10.1101/gr.187501